Individualized medication based on pharmacogenomics and treatment progress in children with IgAV nephritis - Yang, Xuerong; Li, Qi; He, Yuanyuan; Zhu, Yulian; Yang, Rou; Zhu, Xiaoshi; Zheng, Xi; Xiong, Wei; Yang, Yong (Frontiers in Pharmacology, 2022)
Immunoglobulin A vasculitis (IgAV) nephritis, also known as Henoch-Schönlein purpura nephritis (HSPN), is a condition in which small blood vessel inflammation and perivascular IgA deposition in the kidney caused by neutrophil activation, which more often leads to chronic kidney disease and accounts for 1%–2% of children with end-stage renal disease (ESRD). The treatment principles recommended by the current management guidelines include general drug treatment, support measures and prevention of sequelae, among which the therapeutic drugs include corticosteroids, immunosuppressive agents and angiotensin system inhibitors. However, the concentration range of immunosuppressive therapy is narrow and the individualized difference is large, and the use of corticosteroids does not seem to improve the persistent nephropathy and prognosis of children with IgAV. Therefore, individualized maintenance treatment of the disease and stable renal prognosis are still difficult problems. Genetic information helps to predict drug response in advance. It has been proved that most gene polymorphisms of cytochrome oxidase P450 and drug transporter can affect drug efficacy and adverse reactions (ADR). Drug therapy based on genetics and pharmacogenomics is beneficial to providing safer and more effective treatment for children. Based on the pathogenesis of IgAV, this paper summarizes the current therapeutic drugs, explores potential therapeutic drugs, and focuses on the therapeutic significance of corticosteroids and immunosuppressants in children with IgAV nephritis at the level of pharmacogenomics. In addition, the individualized application of corticosteroids and immunosuppressants in children with different genotypes was analyzed, in order to provide a more comprehensive reference for the individualized treatment of IgAV nephritis in children.